2020
DOI: 10.1182/bloodadvances.2020001816
|View full text |Cite
|
Sign up to set email alerts
|

High metabolic heterogeneity on baseline 18FDG-PET/CT scan as a poor prognostic factor for newly diagnosed diffuse large B-cell lymphoma

Abstract: Metabolic heterogeneity (MH) can be measured using 18F-fluorodeoxyglucose (18FDG) positron emission tomography/computed tomography (PET/CT), and it indicates an inhomogeneous tumor microenvironment. High MH has been shown to predict a worse prognosis for primary mediastinal B-cell lymphoma, whereas its prognostic value in diffuse large B-cell lymphoma (DLBCL) remains to be determined. In the current study, we investigated the prognostic values of MH evaluated in newly diagnosed DLBCL. In the training cohort, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 34 publications
3
31
1
Order By: Relevance
“…Interestingly, estimations of intertumoral metabolic heterogeneity (MH) were shown to be an accurate predictor of poor outcomes in patients with higher MTV, coinciding with shorter PFS and OS. Models taking into account both MTV and MH improved upon MTV alone as a predictor for PFS and OS [81,82]. Similar results were found in primary mediastinal B-cell lymphoma (PMBCL), where a model combining both MH and TLG was found to be a more effective predictive tool than models using only one of these parameters [83].…”
Section: [ 18 F]fdg Pet/ctsupporting
confidence: 55%
“…Interestingly, estimations of intertumoral metabolic heterogeneity (MH) were shown to be an accurate predictor of poor outcomes in patients with higher MTV, coinciding with shorter PFS and OS. Models taking into account both MTV and MH improved upon MTV alone as a predictor for PFS and OS [81,82]. Similar results were found in primary mediastinal B-cell lymphoma (PMBCL), where a model combining both MH and TLG was found to be a more effective predictive tool than models using only one of these parameters [83].…”
Section: [ 18 F]fdg Pet/ctsupporting
confidence: 55%
“…However, the study is limited to HL with mediastinal involvement with again small numbers of events. Senjo et al demonstrated that a high metabolic heterogeneity (MH) was a predictor of 5-year PFS and OS in DLBCL across both training (n = 86) and validation cohorts (n = 64) treated at two centres [41]. They found that MH remained a significant predictor for 5-year OS for both cohorts when analysed in multivariate analysis with an ECOG score of >2, and an LDH with a relative risk of 4.75 (95% CI 1.25-18.1) and relative risk of 4.92 (95% CI 1.09-17.03) in the training and validation groups, respectively.…”
Section: Textural and Shape Analysis For Outcome Predictionmentioning
confidence: 99%
“…The simplest example may be to enclose the tumour with ROI, create a histogram of voxel values within the ROI, and calculate mean, standard deviation, energy, entropy, kurtosis, skewness, and so on. A cumulative histogram of SUV and its area under the curve, abbreviated as AUC-CSH, is also commonly used for this purpose [ 50 ].…”
Section: Basic Concepts For Quantitative Fdg Pet Assessmentmentioning
confidence: 99%